Advanced Content Coverage at Kindergarten: Are There Trade-Offs Between Academic Achievement and Social-Emotional Skills?. (August 2019) - Le, Vi-Nhuan; Schaack, Diana; Neishi, Kristen; Hernandez, Marc W.; Blank, Rolf
Policymakers have advocated academic skills building at kindergarten as a way of improving student achievement. However, early childhood educators have concerns with this policy as gains in achievement may come at the expense of children's social-emotional skills. Using a nationally representative data set of kindergartners, we find that advanced academic content, defined as academic skills typically taught at a higher grade, was associated not only with improved math and English/language arts achievement but also with improved social-emotional outcomes. Greater exposure to advanced content was associated with better interpersonal skills, better approaches to learning, better attentional focus, and lower externalizing behaviors. The results suggest that advanced academic content can be taught without compromising children's social-emotional skills.